2012
DOI: 10.1073/pnas.1210251109
|View full text |Cite
|
Sign up to set email alerts
|

Protected areas facilitate species’ range expansions

Abstract: The benefits of protected areas (PAs) for biodiversity have been questioned in the context of climate change because PAs are static, whereas the distributions of species are dynamic. Current PAs may, however, continue to be important if they provide suitable locations for species to colonize at their leading-edge range boundaries, thereby enabling spread into new regions. Here, we present an empirical assessment of the role of PAs as targets for colonization during recent range expansions. Records from intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
185
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 204 publications
(202 citation statements)
references
References 28 publications
13
185
0
4
Order By: Relevance
“…This is concordant with studies which have suggested that PAs will remain important for conservation under climate change [14,15] and provides a contrast to the conclusions of research on alien invasive species, rspb.royalsocietypublishing.org Proc R Soc B 280: 20122310 whose colonizing distributions are typically associated with landscapes affected by human activity [34]. The records that we use here to determine the percentages of birds breeding in PAs are a product of casual observations as opposed to systematic surveys, and we are aware that a bias in observer effort towards PAs could lead to a bias in the proportion of records that come from PAs.…”
Section: Discussionsupporting
confidence: 78%
“…This is concordant with studies which have suggested that PAs will remain important for conservation under climate change [14,15] and provides a contrast to the conclusions of research on alien invasive species, rspb.royalsocietypublishing.org Proc R Soc B 280: 20122310 whose colonizing distributions are typically associated with landscapes affected by human activity [34]. The records that we use here to determine the percentages of birds breeding in PAs are a product of casual observations as opposed to systematic surveys, and we are aware that a bias in observer effort towards PAs could lead to a bias in the proportion of records that come from PAs.…”
Section: Discussionsupporting
confidence: 78%
“…A critical development in modeling a species’ natural resilience (Dawson et al., 2011) and implementing solutions (e.g., Thomas et al., 2012) is mapping and promoting environments to maintain critical standing adaptive genetic variation and the potential generation of novel adaptive alleles; cTNRs offer the potential to support both of these objectives. We present here a methodology by which we were able to identify cTNRs that are potentially the targets of natural selection in a range of mammal species, a taxonomic group underestimated in terms of vulnerability to climate change.…”
Section: Discussionmentioning
confidence: 99%
“…There has been global concern about how these changes might affect protected area networks, one of the main tools used by conservationists to prevent biodiversity loss. Previous assessments of climate change risk to these networks have considered either the presence or representativeness of particular habitats or biomes 5,6 or the distributions of species [7][8][9] . However, to be effective at the species level, protected areas must protect populations large enough to have low extinction risk [10][11][12] .…”
mentioning
confidence: 99%